THE EXPORT PERFORMANCE OF THE EURO AREA: A PANEL QUANTILE REGRESSION APPROACH - Kovačević, Radovan (Economic Annals, 2019)
This paper examines the impact of relevant factors on merchandise exports, volume growth, and the competi-tiveness of euro-area countries. It uses pan-el regressions to explain the development of merchandise exports in the euro-area countries by various price/cost competi-tiveness indicators, development of foreign and domestic demand, and the structure of merchandise exports. A cointegration analysis of panel time series was estab-lished by applying econometric tests and the cointegration equation for the period 1999–2018 was estimated using FMOLS (Fully Modified OLS) and DOLS (Dynamic OLS) estimators. We show that the increase in the share of information communication technology (ICT) product exports in the to-tal merchandise exports of euro-area mem-bers had a positive impact on their export performance. The empirical results show that foreign demand has a positive impact on real merchandise exports, while the esti-mated coefficients decreased from the lower to upper quantiles. The results regarding price and cost competitiveness differ de-pending on the choice of indicators, but in general they are less robust. Therefore, we conclude that in the long run, non-price factors will play an increasingly important role in strengthening the competitive posi-tion of euro-area countries in international markets.